Quantitative Determination of Petroleum Hydrocarbons in Oily Sludge Following Efficient N-Heptane Separation - Zhiwei Zhang; Yun Ma; Chengrong Qin; Xiaoying Liu; Xiangyu Li; Haibo Huang; Shuangquan Yao (BioResources, 2023)
Accurate analysis of the main chemical components of oil-bearing sludge is an important prerequisite for effective soil remediation and resource reuse. However, precise analysis of the extract components is difficult to achieve because of the mutual interference of saturates, aromatics, and resins, collectively called SAR, and asphaltene that are introduced during chloroform extraction. In this study, SAR was efficiently extracted using n-heptane, while asphaltene components were retained in soil because of their insolubility in n-heptane. The maximum yield of SAR extraction was 27.0%, indicating an increase of 1.75% compared to chloroform extraction. The extracted SAR components were separated by chromatography and the main structural units and components were analyzed. The results show that saturates, aromatics, and resins have a single component, a high content of major components, and contain fewer impurities using n-heptane extraction. Moreover, the solubility of asphaltene was inhibited during the effective extraction of SAR components with n-heptane and did not influence the subsequent analysis of SAR component. Efficient SAR extraction, accurate SAR component analysis, and high efficiency asphaltene separation was achieved using n-heptane-extraction-assisted pyrolysis. This provides a new method for the component analysis of oily sludge and promotes its efficient separation.